Daya Oles, Viskositas, Tekstur, dan Warna Selai Bit (Beta vulgaris L.) dengan Penambahan Karagenan Sebagai Bahan Pengental - Dwiloka, Bambang; Latifah, Aini atul; Pranomo, Yoyok Budi (Jurnal Pangan dan Gizi, 2024)
Beetroots have good nutritional content for body health. Beets have the potential to be used as a basic ingredient for jam products. However, to achieve a good quality jam, it is necessary to add carrageenan as a thickening agent to improve the texture of the resulting jam. This research aims to determine the effect of using carrageenan on the spreadability, viscosity, texture and colour of beet jam products. The method used in this research was a Completely Randomized Design (CRD) with 5 treatments and 4 replications, namely giving 1% pectin as a control (P0) and giving different concentrations of carrageenan, namely 0.75% (P1); 0.1% (P2); 1.25% (P3); and 1.5% (P4) in beetroot jam. The results showed that the addition of carrageenan had a significant effect on the spreadability, viscosity, texture and colour of beetroot jam. The addition of 0.75% carrageenan can produce beet jam with better physical characteristics than other treatments.